2019
DOI: 10.3390/ijms20112702
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Motor Neuron-Like Cells from Tonsil-Derived Mesenchymal Stem Cells and Their Possible Application to Neuromuscular Junction Formation

Abstract: Human tonsil-derived mesenchymal stem cells (T-MSCs) are newly identified MSCs and present typical features of MSCs, including having the differentiation capacity into the three germ layers and excellent proliferation capacity. They are easily sourced and are useful for stem cell therapy in various disease states. We previously reported that T-MSCs could be differentiated into skeletal myocytes and Schwann-like cells; therefore, they are a promising candidate for cell therapies for neuromuscular disease. Motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…Previously, we isolated MSCs from tonsillar tissue of children who had undergone a tonsillectomy [37]. TMSCs have been implied for various tissue engineering of the bone [18,38], parathyroid gland [17], pancreatic islet [39], Schwan cells [22], tendon [21], nerve cell [20,23], and skeletal muscle [19] regeneration. For practical applications of cell therapy, it is necessary to obtain a sufficient number of cells through a long-term serial culture [38].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we isolated MSCs from tonsillar tissue of children who had undergone a tonsillectomy [37]. TMSCs have been implied for various tissue engineering of the bone [18,38], parathyroid gland [17], pancreatic islet [39], Schwan cells [22], tendon [21], nerve cell [20,23], and skeletal muscle [19] regeneration. For practical applications of cell therapy, it is necessary to obtain a sufficient number of cells through a long-term serial culture [38].…”
Section: Discussionmentioning
confidence: 99%
“…The replicative senescence induced by the serial culture of TMSCs decreased not only replicative capacity but also the differentiation potential of TMSCs. An examination of three mesodermal differentiation potentials-adipogenesis, osteogenesis, and chondrogenesisrevealed that early-passage TMSCs (passages 5-8) have a superior differentiation potential compared with latepassage TMSCs (passages [20][21][22][23][24][25]. It has also been reported that the quality of other MSCs, such as adipose tissue- [43], bone marrow- [36], and Wharton's jellyderived MSCs [2], were also shown to progressively decline with donor age [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations